Evaluation of the effects of ozone therapy and cisplatin in an experimental model in mice with Ehrlich carcinoma - van der Linden, Laís Albuquerque; Oliveira, Rhaysa Allayde Silva; Serafim, Ykaro Kyokay Vieira; Chaves, Yasmim Theonise Ferreira; Silva, Alluanan Adelson do Nascimento; Santos, Renan Felipe Silva; Santos, Fernando Leandro dos; Souza, Ivone Antônia de; Lima, Evilda Rodrigues de (Medicina Veterinária, 2023)
Ehrlich carcinoma is an aggressive, rapidly-growing tumor used as an experimental model in female mice because it corresponds to mammary adenocarcinoma. The present objective was to evaluate Swiss albino mice (Mus musculus) with Ehrlich carcinoma treated with intrarectal ozone therapy and cisplatin. Twenty-four female mice, approximately 60 days of age, varying between 35g and 43g in weight were divided into four groups, Group 1 (G1): 1mL of cisplatin 2.5mg/kg, orally; Group 2 (G2): Ozone-oxygen mixture (OOM) 20 µg/mL, via rectal insufflation (RI); Group 3 (G3): 1mL of cisplatin 2.5mg/kg, orally+ 20 µg/mL (OOM RI), and Group 4 (G4): control with 1mL of saline 0.9%, orally. All animals underwent an eight-day adaptation period. Forty-eight hours after inoculation, the treatments were performed daily, for six days. The mice were euthanized at the end of the experiment, after treatment, and the tumor was removed. There were statistically significant differences between groups for tumor weight. Mean tumor weight was greater in G4 (3,83 ± 1.20), and lesser in G3 (0.79 ± 0.73). These significant differences were observed between the group G4 and other groups. On histopathology, there were no significant differences between groups. It is concluded that ozone therapy associated with cisplatin proved to be the treatment in which mice with Erhlich's carcinoma showed delay in tumor growth, therefore, the lowest tumor weight.